2006
DOI: 10.1590/s1415-47572006000400029
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mdr isoforms in mice during estrous cycle and under hormone stimulation

Abstract: The multidrug resistance (MDR) phenotype is associated with the expression of P-glycoprotein (Pgp), coded by the multigenic mdr family. Mice present the isoforms mdr1 and mdr3, which are responsible for multidrug resistance, and mdr2, that is involved in the transport of phospholipids. mdr1 expression has more recently been associated also with the secretion of steroid hormones. This work presents an RT-PCR analysis of the expression of mdr isoforms, in several organs of mice during different phases of the est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Similar sex differences in SE induction rate have previously been described in mice (Buckmaster and Haney, 2012) and rats (Mejı́as-Aponte et al, 2002), and are probably not based on sex differences in pharmacokinetics of pilocarpine (Omori et al, 2004). Rather, they may be attributed to sex-dependent sexual hormone levels occurring in the estrus cycle, which have been shown to influence expression levels of PGP (Schiengold et al, 2006). Indeed, evidence suggests that the degree of multidrug transporter-mediated efflux activity at the blood-brain barrier might be sex-related (Morris et al, 2003).…”
Section: Discussionsupporting
confidence: 71%
“…Similar sex differences in SE induction rate have previously been described in mice (Buckmaster and Haney, 2012) and rats (Mejı́as-Aponte et al, 2002), and are probably not based on sex differences in pharmacokinetics of pilocarpine (Omori et al, 2004). Rather, they may be attributed to sex-dependent sexual hormone levels occurring in the estrus cycle, which have been shown to influence expression levels of PGP (Schiengold et al, 2006). Indeed, evidence suggests that the degree of multidrug transporter-mediated efflux activity at the blood-brain barrier might be sex-related (Morris et al, 2003).…”
Section: Discussionsupporting
confidence: 71%
“…1) exhibit some similarities, with higher expression in early-to midluteal phases. This could suggest regulation by steroid hormones during the estrous cycle, as was reported for other ABC carriers such as MDR1 up-regulated by progesterone and repressed by estrogen in mouse endometrium (37). However, in the present study, we have concentrated on possible regulation by OT and IFN known to regulate PG biosynthesis and action at the time of recognition of pregnancy (5,10,38).…”
Section: Discussionmentioning
confidence: 61%
“…Verapamil, a common PGP substrate, showed lower brain uptake in female mice than male mice, suggesting higher PGP expression levels in female mice ( Dagenais et al., 2001 ). Because PGP expression levels are influenced by sexual hormone levels occurring during the oestrus cycle ( Schiengold et al., 2006 ), several studies have reported similar sex-related differences in SE development in both rats and mice ( Mejías-Aponte et al., 2002 ; Morris et al., 2003 ; Buckmaster and Haney, 2012 ). Several studies have implicated the excitatory neurotransmitter glutamate in the underlying mechanism that activates PGP ( Bauer et al., 2007 ; Zibell et al., 2009 ; Hartz et al., 2019 ; Soldner et al., 2019 ).…”
Section: The Limitations Strike Back: Imperfections In the Lithium-pimentioning
confidence: 99%